Association between Induction Start Time and Labor Duration in Nulliparous Women Undergoing Elective Induction of Labor - Facco, Francesca L.; MacPherson, Cora; Reddy, Uma M.; Tita, Alan T.N.; Silver, Robert M.; El-Sayed, Yasser Y.; Wapner, Ronald J.; Rouse, Dwight J.; Saade, George R.; Thorp, John M., Jr; Chauhan, Suneet P.; Costantine, Maged M.; Chien, Edward K.; Heyborne, Kent D.; Srinivas, Sindhu K.; Swamy, Geeta K.; Grobman, William A.; for the Eunice Kennedy Shriver National Institute of Child Health Human Development (NICHD) Maternal-Fetal Medicine Units (MFMU) Network (American Journal of Perinatology, 2025)
This study aimed to examine the association between elective induction of labor (EIOL) start time and labor duration among nulliparous women.The ARRIVE trial was a multicenter randomized controlled trial of induction of labor at 390/7 to 394/7 weeks versus expectant management in low-risk nulliparous women. In this secondary analysis, we included participants randomized to the induction group who had an EIOL without spontaneous labor or rupture of membranes prior to the induction start. The start time of EIOL was categorized as: early a.m. (midnight to 5:59 a.m.), late AM (6 AM–11:59 a.m.), early p.m. (noon–5:59 p.m.), or late p.m. (6 p.m.–11:59 p.m.). The primary outcome was labor duration. Cesarean delivery rates by induction start time were also examined. Multivariable analysis was conducted controlling for age, body mass index, insurance status, and modified Bishop score on admission (<5 or ≥5).Of 3,062 women randomized to EIOL, 2,197 were included in this analysis. EIOL occurred in the early a.m. in 13%, in late a.m. in 28%, in early p.m. in 13%, and in late p.m. in 45%. Participants induced in the late a.m. had the shortest mean labor durations (21.5 ± 11.3 hours) and the highest frequency of delivery at < 24 hours (68%). In adjusted analyses, induction in the late a.m. (vs. grouped other time periods) remained significantly associated with shorter labor duration (−1.5 hours; confidence interval: −2.5 and −0.4; p = 0.006), and there was no interaction between Bishop score and time of EIOL. Cesarean delivery rates did not differ by start time.Induction of labor starting between 6 a.m. and 11:59 a.m. was associated with shorter labor durations, independent of baseline maternal characteristics including cervical status on admission.
Keywords: induction of labor; labor duration; elective induction